High-definition mapping of retroviral integration sites defines the fate of allogeneic T cells after donor lymphocyte infusion - Cattoglio, Claudia; Maruggi, Giulietta; Bartholomä, Cynthia C.; Malani, Nirav; Pellin, Danilo; Cocchiarella, Fabienne; Magnani, Zulma; Ciceri, Fabio; Ambrosi, Alessandro; Kalle, Christof von; Bushman, Frederic D.; Bonini, Chiara; et al. (PLOS ONE, 2010)
The infusion of donor lymphocytes transduced with a retroviral vector expressing the HSV-TK suicide gene in patients undergoing hematopoietic stem cell transplantation for leukemia/lymphoma promotes immune reconstitution and prevents infections and graft-versus-host disease. Analysis of the clonal dynamics of genetically modified lymphocytes in vivo is of crucial importance to understand the potential genotoxic risk of this therapeutic approach. We used linear amplification-mediated PCR and pyrosequencing to build a genome-wide, high-definition map of retroviral integration sites in the genome of peripheral blood T cells from two different donors and used gene expression profiling and bioinformatics to associate integration clusters to transcriptional activity and to genetic and epigenetic features of the T cell genome. Comparison with matched random controls and with integrations obtained from CD34+ hematopoietic stem/progenitor cells showed that integration clusters occur within chromatin regions bearing epigenetic marks associated with active promoters and regulatory elements in a cell-specific fashion. Analysis of integration sites in T cells obtained ex vivo two months after infusion showed no evidence of integration-related clonal expansion or dominance, but rather loss of cells harboring integration events interfering with RNA post-transcriptional processing. The study shows that high-definition maps of retroviral integration sites are a powerful tool to analyze the fate of genetically modified T cells in patients and the biological consequences of retroviral transduction.
Gesehen am 26.01.2023